Memahami Etika Pendidik dan Peserta Didik (Telaah Pemikiran KH. Hasyim Asy’ari dalam Kitab Adab al-'Alim wa al-Muta'allim ) - Hepi Ikmal (Universitas Islam Lamongan, 2020)
Appreciation for the works written by Muslim thinkers in the archipelago is still considerably apprehensive. In fact, there have been many productive Indonesian ulema (Muslim scholars) inheriting the treasury of scholarship. For that reason, the writer tries to study the thinking of KH Hasyim Asy'ari, more specifically about the ethics of educators and learners that he described in the Adab al-'Alim wa al-Muta'allim. The results showed that learners should be able to apply knowledge in accordance with the unity of so-called amaliah (deeds) that uphold the noble moral values integrally. This understanding is be based on his very sharp emphasis on the ethical field of learners. KH. Hasyim Asy'ari requires learners to be obedient and subject to the advice and instruction of their educators. The most obvious portrait of the dynamics of education that applies this view can be seen from some salafi pesantren (Islamic boarding schools) in Indonesia. On the one hand, this view is less reflective of providing opportunities and appreciation to learners, but on the other hand, this view reflects the KH Hasyim Asy'ari's consistent lines of thought genuinely glorifying scholars. Educators as people who have the scientific capacity should be prioritized than the learners